Investigation on the quality of silicon extracted from the Padma river sand using magnesio-aluminothermic process (Bangladesh Journal of Physics, 2020)
Investigation on the quality of the extracted Silicon (Si) from the sand of the Padma river of Bangladesh using the Magnesio-Aluminothermic process has been presented in this work. Magnesio-Aluminothermic process, which is low-energy, low-cost and CO2 free compared to conventional carbothermic process, was used for the extraction of Si from the sand. By performing the thermite process, Si was extracted as a eutectic mixture of Aluminium and Si, following that, several cycles of acid leaching were used to obtain highly pure polycrystalline silicon. After grinding the cleaned sand and making a homogeneous mixture with associated chemicals and ignition materials, modified Aluminothermic reaction was performed to produce a eutectic mixture of Si and Al. Grinded eutectic mixture of Si and Al was then purified with acid leaching and finally above 97% pure crystalline Si was extracted. XRD (X-ray diffraction) and Raman Spectroscopy confirmed the polycrystalline nature of Si where XRF (X-ray fluorescence) and EDX (Energy Dispersive X-ray Spectroscopy) corroborated the high purity of extracted Si describing the chemical composition.Bangladesh Journal of Physics, 26(2), 33-40, December 2019